ANALYSIS OF THE EFFECT OF WORK STRESS, WORK LOAD AND WORK ENVIRONMENT TURNOVER INTENTION - Faturrahman, Faturrahman; Parminto, Ardi; Irwansyah, Irwansyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the effect of work stress, workload and the environment on employee turnover intention of non civil servants. This study uses survey research methods and data collection techniques used are observation, interviews, literature studies and questionnaires. The sample in the study were 100 employees whose sample size was determined through the Slovin formula. The analytical method used is simple regression and multiple regression. From the results of the study, it is known that variable X1 (work stress) partially influences the variable Y (turnover intention). Variable X2 (workload) partially influences the variable Y (turnover intetions). Variable X3 (work environment) partially influences the variable Y (turnover intention). And it is known that variables X1 (work stress), X2 (work load) and X3 (work environment) simultaneously affect variable Y (turnover intention) Keywords: work stress, work load, work environment, turnover intention